Waste Management Education for Children in RT 06 - Ferliando Frisnan Hamid; Bayu Noperanda Abdillah; Wahyu Dwi Saputra; Eko Susilo; Suhendri Suhendri; Ririn Afriani; Hesti Nur'aini; Mimpira Haryono (Jurnal Pengabdian Mandiri, 2026)
Waste is a significant issue in the community, including in RT 06, Pematang Gubernur Village, Bengkulu City. Children's lack of understanding about waste sorting leads to a lot of mixed waste and careless dumping, especially around gutters. This Community Service Program (KKN) aims to increase children's awareness and skills in processing and sorting waste from an early age. The implementation method is an educational approach that includes outreach, material provision, interactive games, and hands-on practice of sorting organic and inorganic waste. The results of the activity indicate an increase in children's understanding and enthusiasm for environmental cleanliness. Children are beginning to differentiate between types of waste and demonstrate a caring attitude towards their surroundings. This program is expected to foster positive and sustainable habits in maintaining environmental cleanliness in RT 06.